Optimisation on biodegradation of glyphosate by locally isolated bacteria - Manogaran, Motharasan (2017)
N-Phosphonomethylglycine (glyphosate) is often used to control weeds in agriculture land. In Malaysia alone, thousands of tonnes of glyphosate formulation is used annually. Although this low-cost herbicide is able to effectively in killing weeds, its extensive use has been negatively linked to the human health due to its toxicity. Moreover, many past studies have reported its negative effects on aquatic animals and vertebrates. Thus, there is a need for an eco-friendly method to manage this environmental contaminant. Furthermore, it is crucial to find glyphosate-degrading microorganisms in the soil of interest for local applications. The objective of this study is to isolate local glyphosatedegrading bacteria and optimisation of culture medium condition to improve the degradation rate. Two bacteria isolated from agriculture site located in Kedah, Malaysia were identified by physical, biochemical and 16S rRNA sequencing techniques as Burkholderia vietnamiensis strain AQ5-12 and Burkholderia sp. strain AQ5-13. These strains were found with the ability to tolerate up to 12 mL/L Roundup concentration and were successfully used to degrade glyphosate. Factors affecting glyphosate biodegradation such as carbon and nitrogen sources, pH of the medium, glyphosate concentration and temperature were optimised using one factor at time (OFAT) and response surface method (RSM) using free cells. Initial free cells of strain AQ5-12 and AQ5-13 were able to degrade 79.7% and 40.67% of 50 ppm glyphosate, respectively, within 24 h incubation. Using these optimisation processes, free cells of AQ5-12 were able to degrade 94% of 100 ppm glyphosate, whereas strain AQ5-13 degraded 94% of 50 ppm glyphosate under optimal condition. The results illustrated fructose at 8.62 g/L, ammonium sulphate at 0.5 g/L, pH 5.41, 100 ppm of glyphosate concentration and 32ºC as the optimum biodegradation conditions required by Burkholderia vietnamiensis strain AQ5-12, whereas the optimum biodegradation conditions for Burkholderia sp. strain AQ5-13 were sucrose at 8.0 g/L, ammonium sulphate at 0.5 g/L, pH 6.0, 50 ppm of glyphosate concentration and temperature at 32ºC. The optimised condition for free cells resulted in significant improvement in degradation rate. The bacteria were immobilised in gellan gum gelling agent with its conditions optimised. The results presented a degradation rate of 87.2% 100 ppm glyphosate with gellan gum concentration of 0.55 g, 285 number of beads and bead size of 0.48 cm for immobilised cells of AQ5-12.Meanwhile, immobilised cells of AQ5-13 illustrated a degradation rate of 96.68% 50 ppm glyphosate with gellan gum concentration of 0.55 g, 280 number of beads and bead size of 0.45 cm. It was seen that immobilised form of bacteria showed better biodegradation in terms of duration as it degrades the glyphosate within 12 h compared to free cells that require 24 h degradation process in optimised media. In conclusion, these strains possess the potential of being used in the management of glyphosate contamination. Furthermore, the success of isolating bacteria from local soils in Malaysia has shown prominent ability in glyphosate degradation rate, which can be applied for glyphosate treatment in agricultural land.